Peran Pondok Pesantren dalam Pengembangan Masyarakat di Era Globalisasi - Ahmad Royani; Dwi Noviani (TAUJIH: Jurnal Pendidikan Islam, 2023)
This article aims to analyze the role of Islamic boarding schools in community development in the era of globalization. So far, Islamic boarding schools are known to be limited to traditional religious educational institutions with kyai and santri components. However, currently, Islamic boarding schools have made great progress in various ways, not only as traditional religious educational institutions but also as pioneers of social transformation. Therefore, this research is important as a vehicle for communicating to the government or the wider community about the role of Islamic boarding schools in their development. Community development is a fundamental concept that underlines many well-established terms such as resource development, rural community development, community economic development, rural revitalization and community-based development. The method used in this research uses a qualitative approach with the nature of library research with data collection techniques obtained through relevant literature: journals, textbooks and online literature. The research results show that the role of Islamic boarding schools has been implemented well in community development, which shows the quality of social relations and planned and gradual progress, such as improving public services and facilities, increasing local government accountability, increasing community participation, improving leadership, building new institutions, and initiate economic and physical development. Keywords: Islamic boarding school, Community Development, Globalization